Empirical Studies on Economics of Innovation, Public Economics and Management Proceedings of the 18th Eurasia Business and Economics Society Conference - Bilgin, Mehmet Huseyin; Danis, Hakan; Demir, Ender; Can, Ugur (Eurasian Studies in Business and Economics, 2017)
XVII, 380 p. 80 illus., 13 illus. in color.